2005
DOI: 10.1007/s00198-005-2012-3
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of the effect of milk basic protein (MBP) supplementation on bone metabolism in healthy menopausal women

Abstract: Milk has more beneficial effects on bone health than other food sources. Recent in vitro and in vivo studies have shown that milk whey protein, especially its basic protein fraction (milk basic protein, MBP), contains several components capable of promoting bone formation and inhibiting bone resorption. The object of this study was to examine the effect of MBP on the bone metabolism of healthy menopausal women. Thirty-two healthy menopausal women were randomly assigned to treatment with either placebo or MBP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 20 publications
4
66
0
2
Order By: Relevance
“…Ten RCTs examined osteocalcin concentrations (Supplemental Table 6) (25,27,28,30,34,35,37,38,61,62). Eight studies (25,27,28,30,35,37,61,62) prescribed milk proteinbased supplements: the doses of milk-based protein in the higher-protein groups in 7 studies ranged from 10 to 45 g/d and 1 study (62) supplemented 250-mg capsules of milk ribonucleaseenriched lactoferrin/d, whereas doses in the lower-protein groups ranged from 0 to 2.1 g milk-based protein/d.…”
Section: Rctsmentioning
confidence: 99%
“…Ten RCTs examined osteocalcin concentrations (Supplemental Table 6) (25,27,28,30,34,35,37,38,61,62). Eight studies (25,27,28,30,35,37,61,62) prescribed milk proteinbased supplements: the doses of milk-based protein in the higher-protein groups in 7 studies ranged from 10 to 45 g/d and 1 study (62) supplemented 250-mg capsules of milk ribonucleaseenriched lactoferrin/d, whereas doses in the lower-protein groups ranged from 0 to 2.1 g milk-based protein/d.…”
Section: Rctsmentioning
confidence: 99%
“…Milk whey protein, especially the fraction with alkaline isoelectric point (milk basic protein, MBP), suppressed bone resorption and prevented bone loss caused by ovariectomy in aged rats (Toba et al, 2000). Supplementation with MBP also increased bone mineral density and suppressed urine levels of bone resorption biomarkers in young women (Aoe et al, 2001;Yamamura et al, 2002;Itabashi, 2006;Uenishi et al, 2007), in menopausal women (Aoe et al, 2005) and in healthy older women (>65 yr; Aoyagi et al, 2010). In particular, MBP directly suppressed osteoclast-mediated bone resorption and led to decreased osteoclast number in animal studies (discussed in Uenishi et al, 2007).…”
Section: Benefits From Milk: Some Experimental Detailsmentioning
confidence: 99%
“…In other words, DPD exhibits a biological reaction regardless of the type of exercise, and the difference in the regression time is influenced by the intensity of the exercise. Aoe et al reported that a 6-month intake of MBP supplements resulted in a reduction in type I collagen cross-linked N-telopeptides (NTx) and suggested that bone improvement was suppressed by bone-resorbing factors [9,10]. Research by Zou et al [11] also showed a reduction in NTx, despite a constant BAP, after MBP supplementation for 8 months.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, consumption of milk basic protein (MBP) supplement and similar dairy products has frequently been used in order to promote bone improvement [9][10][11][12][13]. Of these products, concentrated bovine-milk whey active protein (CBP) has been shown to induce bone formation in vitro, and has attracted interest as a method of bone improvement [12,13].…”
Section: Introductionmentioning
confidence: 99%